Alternative futures for the Northern Flint Hills: scenarios provided by hydrologic modeling - Burkitt, J. Beau (Kansas State University, 2009)
Environmental degradation is a major concern in agricultural landscapes. Innovative tools and methods will be necessary to identify and deal with the ongoing environmental impacts of past and present agricultural practices. The use of scenarios in environmental modeling is one way to address these concerns. Recently a group of researchers devised a framework for creating future land cover scenarios for two physiographic regions in Iowa. Based on that work, a suite of scenarios were created for Antelope Creek watershed in the Northern Flint Hills of Kansas. The Antelope Creek scenarios represent conditions pre Euro-American settlement, present day, increased intensification of agricultural production, enhancement of water quality, and enhancement of biodiversity. These scenarios were then modeled using the Soil and Water Assessment Tool (SWAT). Additional model runs were completed to compare SSURGO and STATSGO soil datasets. Results indicated that reductions in discharge, total suspended sediment and various nitrogen and phosphorus loads could be achieved by implementing modest changes to agricultural management practices. Results also indicated that a higher detail soil dataset such as SSURGO lead to slightly higher loads than with STATSGO data.
Keywords: Ecological scenarios; Hydrologic modeling; Water quality; Alternative futures; Engineering, Environmental (0775); Environmental Sciences (0768); Physical Geography (0368)